2005
DOI: 10.1080/13803610500110174
|View full text |Cite
|
Sign up to set email alerts
|

What Money Can Buy: Examining the effects of prepaid monetary incentives on survey response rates among college students

Abstract: This study examined the effects of prepaid monetary incentives on college students' rate of responding to a survey designed to assess beliefs and values. It also assessed the extent to which incentive effectiveness depended on such student characteristics as gender, race, and socioeconomic status. The findings suggest that $2 incentives enhance response rates over $0, but that $5 incentives do not substantially improve response rates over $2 incentives. Further, although the descriptive findings suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
2
11
1
Order By: Relevance
“…Although previous research has shown that college students who received a $5 or $2 incentive with a questionnaire were more likely to respond (41% and 36%, respectively) than those who receive no incentive (23%) 12 , we did not find any significant differences in response rates among age groups or within the college-aged individuals.…”
Section: Discussioncontrasting
confidence: 53%
“…Although previous research has shown that college students who received a $5 or $2 incentive with a questionnaire were more likely to respond (41% and 36%, respectively) than those who receive no incentive (23%) 12 , we did not find any significant differences in response rates among age groups or within the college-aged individuals.…”
Section: Discussioncontrasting
confidence: 53%
“…Szelényi, Bryant and Lindholm (2005) suggest that a response rate of 32% is acceptable in self-report surveys such as the present one. A description of the scales used is outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained in this study were analysed by the statistical consultation service of the North-West University in Potchefstroom, South Africa, by means of SPSS for Windows version 17 (SPSS, 2005). Descriptive statistics and Cronbach alpha reliability coefficients were determined for all scales and sub-scales used.…”
Section: Discussionmentioning
confidence: 99%
“…For non-denominational churches, we were able to locate online confessions of faith or church doctrinal statements and coded these Evangelical if there were mentions of biblical inerrancy and necessity of being born again (Wilcox and Larson 2006;Smith 1990;Layman 2001;Wald and Calhoun-Brown 2007). From this list, we randomly selected 20 churches, and over-sampled four additional Evangelical churches, as we expected a lower response rate (Szelenyi, Bryant, and Lindholm 2005). We sent letters to these 24 churches, detailing our project, purposefully requesting the participation of a small group and notifying them of a follow-up call (Creswell 2008).…”
Section: Methodsmentioning
confidence: 99%